Fungal Infection among Diabetic and Nondiabetic Individuals in Nepal - Saud, Bhuvan; Bajgain, Prajuna; Paudel, Govinda; Shrestha, Vikram; Bajracharya, Dipendra; Adhikari, Saroj; Dhungana, Gunaraj; Awasthi, Mamata Sherpa (Interdisciplinary Perspectives on Infectious Diseases, 2020)
Background. Low immunity, comorbid clinical conditions, and metabolic disorders may be the underlying factors that determine the severity of infection. Diabetes increases the risk of infection and multiple organ damage. In Nepal, the actual burden of fungal infections has not been estimated or is in a limited progress. This study aimed to investigate the status of fungal infection in diabetic and nondiabetic individuals in Bhaktapur, Nepal. Materials and Methods. A total of 670 samples were collected from 134 participants. From each participant, five samples were collected from different sites like an oral wash, toe swab, midstream urine, hair shaft, and nail scrapings. All samples were cultured on Sabouraud dextrose agar. Gram stain was used to observe yeast cells and lactophenol cotton blue stain was used for hyphae. Chlamydospore production by Candida species was observed in cornmeal agar medium by Dalmau Plate method. Candida species isolated were characterized by germ-tube test and differentiated using CHROM agar Candida medium. Candida species isolates were tested for antibiotic susceptibility. Results. Overall, 19.4% of the samples showed fungal growth. The prevalence of fungal infection was higher in diabetic (34.0%) than nondiabetic individuals (4.7%). Fungal growth was found to be higher in oral wash followed by toe, urine, hair, and nail samples. Predominant fungi were Candida species (57.5%), Aspergillus species (28.4%), and Trichophyton species (10.7%). Oral wash, toe, and urine samples in diabetics had a significantly higher fungal prevalence when compared between both groups, p value < 0.05. In Candida isolates, higher resistance was seen against fluconazole 36.8% and ketoconazole 28.9%, whereas other drugs showed low resistance. Conclusion. Diabetic participants are more susceptible to fungal infection than the nondiabetics. Overall, Candida species and Aspergillus species are highly predominant fungi. Candida species are highly resistant to fluconazole and ketoconazole.